Epidemiological Characterization and Risk Assessment Associated with the Presence of Diptera Order in Laying Poultry Farms - Oliveira, Tiago Mendonça de; Teixeira, Cristina Mara; Araujo, Isabela de Lourdes; Rezende, Leandro do Carmo; Cunha, Lucas Maciel; Filho, Rui Pitágoras de Lima Castro; Diniz, Soraia Araújo; Silva, Marcos Xavier (Acta Scientiae Veterinariae, 2018)
Background: Health aspects of flocks of laying chickens, such as the occurrence of infestations by parasites and poultry pests, influence significantly the productivity indicators. In recent years, Brazilian poultry has gone through a scientific and technological evolution which resulted in high density poultry hens in the laying sheds and an increase of the occurrence of ectoparasites such as Diptera. The presence of these flies have caused negative impacts for poultry farming, since these may be responsible for the increase of stress and disease emergence and, in addition, reduction of productivity. In this context, the control of synanthropic Diptera is one of the challenges of the poultry farmers and professionals of this area. This study was carried to assess and characterize the risks for the presence of flies in chicken houses of laying farms in the state of Minas Gerais. Materials, Methods & Results: Was used a secondary database and adapted for this study, with information from 402 chicken houses of 42 laying hens commercial properties. The variables used to compose the correspondence model were selected through chi-square tests (P ≤ 0.05). A risk index was built to the presence of flies from variables considered as risk factors for these ectoparasites. In addition, a study of the spatial analysis was carried to evaluate the intensity of chicken houses of poultry farms with the presence of flies. For this, a Kernel map was produced using the QGIZ 2.18.1 software, georreferencing the regions of state of Minas Gerais that have these ectoparasites. It was observed the presence of flies in 253 chicken houses evaluated, which corresponds to a frequency of 62.9%, with the most present flies were Chrysomya spp. 37.3%, M. domestica 34.3%, Fannia spp. 16% and Stomoxys spp. 14%. The graph of the correspondence analysis produced for the epidemiological characterization of the presence of flies presented an accumulated chi-square value of 56.05%. There was an association of the risk index with removal interval and the humidity of the manure and with the type of installation of chicken houses. Farms with chicken houses that create their birds on the ground present a lower risk for the presence of Diptera. In addition, when the removal of the manure is performed manually and is not done periodically, the presence of flies in the chicken houses is observed. It was verified that clusters located in the messoregion south/southwest of Minas Gerais and between the west and metropolitan mesoregion of Belo Horizonte with chicken houses that have the presence of flies. Discussion: The accumulation and permanence of manure can occur in less technical farms that have laying hens kept in confinement with high densities. In the case of Diptera, the greater the interval of removal of the manure below cages, the greater the risk for their presence, combined with the high densities of the birds that contribute to a faster accumulation of manure. The humidity of the manure is another important factor for the development of flies. The risk is high when chicken feces are liquefied, due to the fact that larvaes of flies need a moist substrate for survival. These results provide knowledge about the epidemiology of flies, in addition to demonstrate the profile of laying farms in the state of Minas Gerais. The implementation of certain management measures and the investment in technification of the chicken houses could reduce the risks of possible infestations in the flocks, besides the negative effects resulting from this ectoparasitism.